Quo Vadis, Europa? Four paths and their plausibility - Adrienne Héritier (International Trade, Politics and Development, 2019)
Purpose – The purpose of this paper is to assess the plausibility of four different mid-term paths of development of the European Union (EU): first, a political union or a European state; second, a differentiated and flexible integration of the polity; third, a covert and deepening integration of the polity outside of the political arenas; fourth, the disintegration and/or dissolution of the EU through the exit of individual members or a joint decision to terminate the union. Design/methodology/approach – The paper uses strategic interaction analysis to identify the plausibility of each of these four possible outcomes. By systematically varying the relevant actors’, i.e. European Council’s and member states’, the European Parliament’s, the Commission’s, preferences over outcomes while holding constant institutional rules of decision making on the one hand, and systematically varying institutional rules on the other while holdings actors’ preferences constant, the paper comes to the conclusion that differentiated and flexible integration and covert integration are the most plausible mid-term paths of development. Findings – The paper finds that neither a European state or deep political union nor a disintegration or even dissolution of the EU is the most plausible path of development. Rather, it concludes that flexible and differentiated integration as well as covert integration outside the political arenas are the most likely developments. However, it also draws attention to the political costs of flexible and differentiated integration which does not allow for an overall view of political and policy issues negotiated at one political table, limiting the scope of compromise formation and even leading to a fragmented polity. Covert integration consisting of mechanisms of hidden integration “invisible” to the wider public may lead to a democratic backlash, once citizens realize that integration has considerably deepened without their being aware of it. Originality/value – Most publications regarding the future development of the EU are normatively driven, either conjuring an imminent disintegration, or invoking the necessity of a deepening integration leading to a political union. This paper, by contrast, seeks to assess the likely further development based on empirically identified factors and a logical argument.